2021
DOI: 10.1002/app.51525
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun cellulose fibers from ionic liquid: Practical implications toward robust morphology

Abstract: Fibrous matrix of cellulose was obtained by wet-type electrospinning of cellulose in ionic liquid, 1-butyl-3-methylimidazolium acetate (BMIMAc). The experiments were designed to determine the effects of electric field intensity and the amount of dissolved cellulose on cellulose fiber morphology and diameter. Taking to account practical implications, that is, fiber size and the effectiveness of production, the most effective production of fibers took place using 3% cellulose/BMIMAc solution at electric field of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…In addition, the chemical property, such as the infrared spectrum of the electrospun cellulose fibers showed almost no difference from the spectrum of the virgin cellulose. This indicated that the cellulose retained its original chemical structure, as well as [C 4 mim][OAc] and the washing solvents which were adequately leached from the electrospun cellulose fibers [6]. Nevertheless, the crystalline property, such as the intensity of the X-ray diffraction peak of the electrospun cellulose fibers is significantly decreased, compared to the virgin cellulose (Figure 6a).…”
Section: Properties Of Electrospun Biodegradable Polymer Fibers Assis...mentioning
confidence: 94%
See 3 more Smart Citations
“…In addition, the chemical property, such as the infrared spectrum of the electrospun cellulose fibers showed almost no difference from the spectrum of the virgin cellulose. This indicated that the cellulose retained its original chemical structure, as well as [C 4 mim][OAc] and the washing solvents which were adequately leached from the electrospun cellulose fibers [6]. Nevertheless, the crystalline property, such as the intensity of the X-ray diffraction peak of the electrospun cellulose fibers is significantly decreased, compared to the virgin cellulose (Figure 6a).…”
Section: Properties Of Electrospun Biodegradable Polymer Fibers Assis...mentioning
confidence: 94%
“…Table 7 shows the properties of electrospun biodegradable polymer fibers were assisted by ionic liquids as solvents. The electrospun cellulose fibers were prepared by Ciuzas et al from raw cellulose fibers using [C 4 mim][OAc] as a solvent [6]. The morphological, chemical, crystalline, and thermal properties of the prepared electrospun fibers were characterized by a scanning electron microscope (SEM), Fourier transform infrared spectrometer, X-ray diffractometer (XRD), and thermal gravimetric analyzer.…”
Section: Properties Of Electrospun Biodegradable Polymer Fibers Assis...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, its high melting point combined with its low vapor pressure requires application of wet electrospinning, as common dry electrospinning is not capable of producing the desired NFs. By doing this, the electrospun fibers slowly solidify in a coagulation bath, in which the ionic liquid is replaced by a co-solvent, which is later removed by desiccation or freeze-drying (Quan et al 2010;Ciuzas et al 2021). Quan et al (2010) evaluated the electrospinning of cellulose dissolved in a hydrophilic ionic liquid, 1-butyl-3-methylimidazolium chloride (BmimCl), and also the influence of dimethyl sulfoxide (DMSO) as an additive in solutions with a higher concentration of cellulose.…”
Section: Electrospinning Of Cellulosementioning
confidence: 99%